Natural and vaccine-induced immunity are equivalent for the protection against SARS-CoV-2 infection - Matteo Franchi; Giacomo Pellegrini; Danilo Cereda; Francesco Bortolan; Olivia Leoni; Giovanni Pavesi; Massimo Galli; Giuseppina Valenti; Giovanni Corrao (Elsevier, 2023)
Objectives: To compare the long-term cumulative risk of SARS-CoV-2 infection associated with natural and vaccine-induced immunity. Methods: Retrospective population-based cohort study based on registry of COVID-19 vaccinations and SARS-CoV-2 infections among 9.1 million citizens of Lombardy, Italy, eligible for vaccination on 27th December 2020. Those who developed SARS-CoV-2 infection from 24th May to 14th September 2021, provided they did not yet receive the COVID-19 vaccine when infection was confirmed, and those who received the second mRNA vaccine dose, provided they had not yet developed the infection, were selected to be 1:1 matched for sex, age and index date. The latter corresponded to 90 days after confirmed infection or 14 days after vaccine administration. A control cohort including citizens who, on the index date, had neither developed infection nor received vaccination was also selected. Kaplan-Meier curves were used for comparing the cumulative incidence of new SARS-CoV-2 infection from the index date until 22nd June 2022. Results: Overall, 19,418 1:1:1 risk-sets were included. After 9 months of follow-up, the cumulative risk of new SARS-CoV-2 infection was 21.8%, 22.0%, and 25.9%, respectively, among exposed to natural immunity, vaccine-induced immunity and unexposed. Conclusions: Equivalent potential for protecting against new SARS-CoV-2 infection was observed.